Exposed Subcutaneous Implantable Devices. Issue 3 (March 2015) - Toia, Francesca; D'Arpa, Salvatore; Cordova, Adriana; Moschella, Francesco
<x xml:space="preserve">Abstract</x> Background: Implantable venous and electrical devices are prone to exposure and infection. Indications for management are controversial, but—especially if infected—exposed devices are often removed and an additional operation is needed to replace the device, causing a delay in chemotherapy and prolonging healing time. We present our protocol for device salvage, on which limited literature is available. Methods: Between 2007 and 2013, 17 patients were treated (12 venous access ports, 3 cardiac pacemakers, and 2 subcutaneous neural stimulators). Most patients were operated within 7 days from exposure. All patients received only a single perioperative dose of prophylactic antibiotic. In cases of gross infection (n = 1), the device was immediately replaced. In the absence of clinical signs of infection: Complete capsulectomy and aggressive cleaning with an n-acetylcysteine solution and saline solution. Primary exposure of venous ports with sufficient skin coverage (n = 10): the device was covered with local skin flaps. Recurrent cases, cases with insufficient skin coverage or big devices (n = 7): the device was moved to a subpectoral pocket. Mean follow-up was 19 months. Results: Sixteen devices were saved. Only one grossly infected pacemaker was removed and replaced immediately. Only in 1 case, exposure of a venous port recurred after 18 months and was successfully moved to a subpectoral pocket. Chemotherapy was always restarted as scheduled and electrical devices remained functional. Conclusions: This protocol allows—with a straightforward operation and simple measures—to save exposed devices even several days after exposure. Submuscular placement or immediate replacement is indicated only in selected cases.